Effects of chemical additives on the hydration behaviour of cement composites from calamus and laccosperma canes (2011)
"The effects of calcium chloride (CaCl2) and Magnesium Chloride(MgCl2) on the maximum hydration temperature (Tmax) setting time(tmax) and Time ratio (tR) of Calamus deerratus and Laccosperma secundiflorum particles mixed with Portland cement was investigated. Particles of ratten canes were mixed with cement, water and chemical additives. Hydration tests were performed in thermally sealed thermos flasks while hydration parameters:Tmax and tmax were measured after 24 hrs. The tmax, Tmax and tg ranged between 25.7 to 26.5 hrs,43.1 to 46.6o C and 3.6 to 3.7 respectively without pre-treatment and were between 7.4 to 23.1 hrs,49.3 to 65.7 oC and 1.0 to 3.0 respectively when pre-treated with chemical additives. Findings showed that untreated ratten generally inhibited cement setting probably due to inherent sugar content. Particles of laccosperma canes inhibited cement setting more than those of the Calamus canes. The addition of both CaCl2 and MgCl2 significantly improved the Tmax but reduced the tmax and tr of the ratten-cement mixes. Addition of CaCl2 enhanced the hydration behaviour of the ratten composites more than MgCl2. "